1996
DOI: 10.1055/s-2008-1071013
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis After Blunt Abdominal Trauma: Cause or Coincidence?

Abstract: The association of appendicitis and blunt abdominal trauma (BAT) is an exceptionally rare occurrence with a few case reports in the literature. The main question whether this association is a result of causative or coincidental relationship has not been evaluated among children. A retrospective clinical study was performed to clarify the pathogenesis, incidence, clinical characteristics and outcome of appendicitis diagnosed in children during the hospitalization period following blunt abdominal trauma (BAT). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 0 publications
0
16
0
2
Order By: Relevance
“…In both cases, blunt abdominal trauma has produced appendiceal edema with inflammation and hyperplasia of appendix lymphoid tissue, and then, obstruction of the appendiceal lumen, leading to acute appendicitis [4]. Ciftçi and al reported 5 cases of appendicitis occurring after abdominal trauma suggesting the same mechanism [2]. It is well known that intra-abdominal pressure increases in varying degrees in every blunt abdominal trauma case [5,6,7].…”
Section: Discussion:-mentioning
confidence: 99%
“…In both cases, blunt abdominal trauma has produced appendiceal edema with inflammation and hyperplasia of appendix lymphoid tissue, and then, obstruction of the appendiceal lumen, leading to acute appendicitis [4]. Ciftçi and al reported 5 cases of appendicitis occurring after abdominal trauma suggesting the same mechanism [2]. It is well known that intra-abdominal pressure increases in varying degrees in every blunt abdominal trauma case [5,6,7].…”
Section: Discussion:-mentioning
confidence: 99%
“…In 1938, Fowler 2 reported only 48 cases out of 13,496 cases of appendicitis (0.3%) with a history of trauma. Ciftci et al 5 reported only five cases of appendicitis out of 554 patients (0.9%) following blunt abdominal trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Karın ağrısı nedeniyle hastaneye getirilirken trafik kazası geçiren ve akut karın ön tanısıyla yapılan ameliyatta kökünden kopmuş enfekte apandiks saptanan 1 olgu (186) dışında; 7 merkezden toplam 15 olguda apandektomi yaralanma ile ilişkilendi-rilmiştir (85,113,114,137,138,153,171,186,224,316,317) . Bu olgulardan histopatolojik incelemede apandisit saptanan 5'inden 3'ü radyolojik incelemelerde apandisit tanısı konarak (171,153,224) , diğer 2'si ise künt karın yaralanması nedeniyle (137,138,316,317) ameliyat edilmiştir.…”
Section: Yaralanmaunclassified
“…Bu 5 olgunun 3'ünde fekalit bulunması dikkat çekmiştir. Kalan 10 olgu künt karın yaralanması nedeniyle ameliyata alınmış; bunlardan 3'ünde apandiks mezo yırtılması (85) , 7'sinde ise apandikste ödem, hiperemi, hematom (85,113,114) nedeniyle apandektomi yapılmıştır. İki merkez verilerine dayanılarak künt karın yaralanmalı olgularda yaralanmış apandiks bulunma sıklıkları 5/554 (%0,9) ve 5/117 (%4) olarak belirlenmiştir (85,113,114) .…”
Section: Yaralanmaunclassified